Enhanced Suffix Stripping Algorithm to Improve Information Retrieval - Singh, Sundar; Pateriya, RK (International Journal of Computer Sciences and Engineering, 2025)
Stemming algorithms are used to convert the words in text into their grammatical base form, and are mainly used to increase the Information Retrieval System’s efficiency. Several algorithms exist with altered techniques. The most widely used is the Porter Stemming algorithm. However, it still has several drawbacks, although many attempts were made to improve its structure. This paper discloses the inaccuracies encountered during the stemming process and proposes the corresponding solutions.